Digital Signal Processing: A Hands-On Approach (sách photo) - Charles Schuler (McGraw -Hill, 2003)
This new book is intended for two-year and four-year electronics students, as well as industry practitioners who need to learn about applied Digital Signal Processing. The text has a very practical "hands-on" approach, appropriate for those students who will apply and troubleshoot modern electronic systems. The authors present critical ideas and then apply them to real-world technician work via software simulations and examples. These activities will clearly illustrate core concepts to increase understanding and aid retention. The CD-ROM included with the text contains five programs that support the hands-on activities. Three of the programs were specially prepared for beginners just learning DSP; two present demo versions of professional software used by DSP designers. --This text refers to the Paperback edition.